Distance Teaching of Masters in the Context of Life-long Education - Sharan, Ryslan (Pedagogical Discourse, 2011)
The problem of distance teaching of Masters in the context of life-long education is researched in the article. There has been characterized the influence of rapid technological development, dynamic integration social and economic processes on the existing traditional educational systems. There have been analyzed conceptual theories of distance education. There has been substantiated the possibility of realizing principles and models of open teaching for Masters on condition of wide-scale implementation of distance education techniques into educational system.